Workflow Intervals of Endovascular Acute Stroke Therapy During On- Versus Off-Hours: The MR CLEAN Registry. Issue 10 (October 2019) - Hinsenveld, Wouter H.; de Ridder, Inger R.; van Oostenbrugge, Robert J.; Vos, Jan A.; Groot, Adrien E.; Coutinho, Jonathan M.; Lycklama à Nijeholt, Geert J.; Boiten, Jelis; Schonewille, Wouter J.; Dippel, Diederik W.J.; van der Lugt, Aad; Majoie, Charles B.L.M.; et al.
Abstract : Background and Purpose—: Endovascular treatment (EVT) of patients with acute ischemic stroke because of large vessel occlusion involves complicated logistics, which may cause a delay in treatment initiation during off-hours. This might lead to a worse functional outcome. We compared workflow intervals between endovascular treatment–treated patients presenting during off- and on-hours. Methods—: We retrospectively analyzed data from the MR CLEAN Registry, a prospective, multicenter, observational study in the Netherlands and included patients with an anterior circulation large vessel occlusion who presented between March 2014 and June 2016. Off-hours were defined as presentation on Monday to Friday between 17:00 and 08:00 hours, weekends (Friday 17:00 to Monday 8:00) and national holidays. Primary end point was first door to groin time. Secondary end points were functional outcome at 90 days (modified Rankin Scale) and workflow time intervals. We stratified for transfer status, adjusted for prognostic factors, and used linear and ordinal regression models. Results—: We included 1488 patients of which 936 (62.9%) presented during off-hours. Median first door to groin time was 140 minutes (95% CI, 110–182) during off-hours and 121 minutes (95% CI, 85–157) during on-hours. Adjusted first door to groin time was 14.6 minutes (95% CI, 9.3–20.0) longer during off-hours. Door to needle times for intravenous therapy were slightly longer (3.5 minutes, 95% CI, 0.7–6.3) during off-hours. Groin puncture to reperfusion times did not differ between groups. For transferred patients, the delay within the intervention center was 5.0 minutes (95% CI, 0.5–9.6) longer. There was no significant difference in functional outcome between patients presenting during off- and on-hours (adjusted odds ratio, 0.92; 95% CI, 0.74–1.14). Reperfusion rates and complication rates were similar. Conclusions—: Presentation during off-hours is associated with a slight delay in start of endovascular treatment in patients with acute ischemic stroke. This treatment delay did not translate into worse functional outcome or increased complication rates. Abstract : Supplemental Digital Content is available in the text.